Optimization of RNA Extraction Method of Banana Leaf Using Li Buffer and GENEzol Reagent - Kusumaningtyas, Ida Ayu Mas Amelia; Pambudi, Arief; Effendi, Yunus (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
High quality extracted RNA from plant tissues is used in downstream transcriptomic application that needs high quantity for multiple analysis. Attaining high quality and high yield for banana plant tissue is a challenge with its high number of secondary metabolites becoming contaminants, effecting the purity of RNA extracted. A procedure to extract banana plant RNA with high quality and quantity in this study is developed to be simple, robust, affordable and accessible using basic lab equipment and materials. This study optimizes RNA extraction from the leaf of juvenile Pisang Susu (Musa spp.) using a combination of Li buffer (modified CTAB) and GENEzol reagent. Treatment differs in the use of β-mercaptoethanol and the duration of sample precipitation with isopropanol. NucleoSpin RNA Plant extraction kit was made as comparison. Measurement of RNA quantity used quantus fluorometer, and quality measured by spectrophotometer. Results showed that the addition of β-mercaptoethanol in Li buffer is vital with samples left to precipitate overnight providing best results. The total RNA obtained had a higher yield compared to the commercial kit with 108 – 211 ng/µl and 0.35 – 0.37 ng/µl respectively. Light absorbance A260/280 indicating sample purity between method has similar RNA quality of 0.917 – 1.084 and 0.843 – 1.026. This study proved that modification of CTAB buffer using Li buffer for RNA extraction resulted in better quality and quantity of RNA compared to the commercial RNA extraction kit.Keywords – Banana, Optimization, RNA Extraction.